(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2026)
Over the past few years, Iraq has seen significant developments in digital financial services, which have begun to influence how individuals manage their money—particularly in terms of saving and investing. This study explores how digital financial inclusion has impacted individual financial behavior in Iraq between 2019 and 2024, by analyzing a sample of banks and electronic payment companies. The research examines the role of digital tools—such as mobile wallets, online banking, and electronic payment platforms—in shaping people’s financial habits. It also considers how these technologies have helped include more individuals in the formal financial system, especially those who previously lacked access to traditional banking services. To carry out this analysis, the study relies on a mix of quantitative and qualitative data collected from both financial institutions and users of digital financial services. The findings suggest a growing trend in the use of digital financial services across different social groups, driven by increased smartphone usage, government efforts to promote financial digitization, and changing attitudes toward technology. The results also indicate a clear link between access to digital financial services and more active saving and investment behaviors—though this link varies depending on age, education level, and income. In conclusion, the study emphasizes the importance of investing in digital infrastructure and promoting financial literacy to support a broader and more inclusive financial environment. Doing so could play a key role in achieving long-term economic development in Iraq.